Fast elimination of cable fire smoke in underground tunnels using acoustic agglomeration technology. (November 2021) - Yuan, Dingkun; Zhang, Guangxue; Lin, Chenyu; Lv, Hongkun; Zhang, Kang; Lin, Fawei; Gu, Hailin
Graphical abstract: Highlights: Smoke production characteristics of typical electric cables are studied. Elimination of cable fire smoke by acoustic agglomeration is demonstrated. The extinction coefficient reaches the safety escape threshold after only 60 s. The optimal frequency for the agglomeration of cable fire smoke is 1.5 kHz. Abstract: Reduction in light transmittance and visibility due to the obscuration of fine smoke particles has been regarded as the most critical threat to fire life safety. Therefore, it is essential for smoke control in underground spaces where electric cables are installed, especially for cable tunnels, underground utility tunnels, subway tunnels, etc. This paper presents a new method of fast elimination of cable fire smoke in underground tunnels using acoustic agglomeration technology. First, the smoke production characteristics of typical electric cables are studied. It is found that the light transmittance drops to 20% after burning for about 60 s. Comparing to vertical burning, more smoke is produced when the cables are burned horizontally. Then, the elimination effect of cable fire smoke is investigated experimentally. Typically, the light transmittance is rapidly increased from 10% to 60% in 11 s, and then reaching the threshold of safe escape in fire situation in only 60 s, at an optimal frequency of 1.5 kHz and an acoustic power of 12 W. In the acoustic agglomeration process, acoustic frequency significantly influences the time required for a light transmittance to reach a given value. The elimination effect is promoted with the acoustic power until the corresponding secondary acoustic effects become significant.